Perceptions of pre-service English teachers towards the use of digital badges - Basal, Ahmet; Kaynak, Naime Elcan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
The use of digital badges has become increasingly common in educational settings as an alternative assessment tool, and they are linked with student motivation and integration of gamification elements into learning environments. This study explores the perceptions of pre-service English teachers at a university of the inclusion of digital badges in an LMS used in their face-to-face courses. Seventy-nine prospective English teachers participated in the 14-week study employing a mixed method design in which data were collected through a questionnaire and open-ended questions. Quantitative data analysis suggests that the participants had positive perceptions of the use of digital badges as an integral part of their courses. Content analysis of the qualitative data generated themes demonstrating teacher candidates' perceptions of digital badges. Overall, the study provides some implications for using digital badges as well as caveats to be taken into account in planning their use.
Keywords: Assessment; digital badges; perception; gamification; pre-service English teachers; STUDENTS; Education & Educational Research